University disputes for today and tomorrow?: political polarization and weak teaching - Cabrera Di Piramo, Carolina; Regueira Domínguez, Avril (Revista Internacional de Teoría e Investigación Educativa, 2025)
The aim of this paper is, from the field of knowledge production in Higher Education and in dialogue with contributions from other areas of knowledge, to discuss some current university conflicts or issues. Through a theoretical and conceptual overview, we attempt to develop a framework that encompasses some current social changes and challenges and problems identified in and for universities around the world. We focus specifically on the problems arising from the links between democracy and universities as a consequence of processes that have been taking place in universities for several decades. We analyze this issue through a concrete example: the recent case of Uruguay. We attempt to provide examples of political polarization processes and changes in teaching practice that can undermine the full democratic practice of universities and the dialogue between universities and their society. Beyond the specific case, we debate some impacts that the consolidation of these changes may have on the university's missions or responsibilities in establishing itself as a protected space for the pursuit of debate and civic engagement.
Keywords: university; democracy; political polarization; teaching work